Региональные особенности фауны голых жаброногов и щитней (Crustacea, Phyllopoda) внетундровой территории европеской части России и Украины - Вехов, Н.В.; Вехова, Т.П. (Вестник зоологии, 1993)
Zonal distribution regularities, possible ways of origin and habital preference of Anostraca and Notostraca are considered on the base of 2384 samples from 702 water bodies collected in 1985—1992.